Construction life cycle assessment methods and their key features - Syvolap, Y.; Tytok, V. (Ways to Improve Construction Efficiency, 2023)
The article examines the methods of assessing the life cycle of construction, as well as defines their key features and role in the strategic management of construction projects. Key features include a comprehensive approach to assessing the impact of construction projects on areas such as the economy, environment and society. The application of life cycle methods in the construction industry is related to: the assessment of the effectiveness of the implementation of construction objects and the need to work out the issue of financial planning and budgeting, taking into account not only the costs of construction, but also the costs of operation and disposal; with the analysis of investment risks, which are extremely important in solving socio-economic issues; implementation of mutually beneficial cooperation schemes between state structures and the private sector; on the attraction of foreign investments in the economy of the state. Analysis of specific construction materials and technologies at different stages of the life cycle can serve as a basis for developing recommendations for choosing materials with a lower environmental impact. The integration of life cycle assessment (LCA) methods with other sustainability and environmental impact assessment methods allows creating more comprehensive approaches to the analysis of objects, services or projects. The results of the research can be used in the development of practical recommendations for builders, designers and other industry participants regarding the use of environmentally friendly materials, technologies and construction methods. The creation of training schools and conditions for the successful implementation of life cycle assessment technologies in the construction industry is extremely important to ensure effective and sustainable development.